Arqueologia histórica nas Missões de Santo Ângelo: representações dos dirigentes municipais sobre as escavações arqueológicas e políticas públicas de patrimônio (2006-2007) - Domanski, Andressa (2013)
The dissertation studies the cultural representations on the archaeological researches related to Cultural Research Management (CRM) undertaken from 2006 to 2007 in the Pinheiro Machado Square, an archaeological site located in the Ancient Reductions of Santo Ângelo, Rio Grande do Sul, Brazil. From an Oral History point of view, the study aims to know mainly the cultural representations about of the city hall‟s staff of the Santo Ângelo